Antiproliferative, anti-inflammatory and antioxidant activities of leaf extracts, fractions and isolated compounds from Ptaeroxylon obliquum - McGaw, Lyndy Joy (University of Pretoria, 2023)
Thesis (PhD (Phytomedicine Programme))--University of Pretoria, 2022.